Brain and spinal cord injury repair by implantation of human neural progenitor cells seeded onto polymer scaffolds - Shin, Jeong Eun; Jung, Kwangsoo; Kim, Miri; Hwang, Kyujin; Lee, Haejin; Kim, Il-Sun; Lee, Bae Hwan; Lee, Il-Shin; Park, Kook In (Experimental & molecular medicine, 2018)
Hypoxic-ischemic (HI) brain injury and spinal cord injury (SCI) lead to extensive tissue loss and axonal degeneration. The combined application of the polymer scaffold and neural progenitor cells (NPCs) has been reported to enhance neural repair, protection and regeneration through multiple modes of action following neural injury. This study investigated the reparative ability and therapeutic potentials of biological bridges composed of human fetal brain-derived NPCs seeded upon poly(glycolic acid)-based scaffold implanted into the infarction cavity of a neonatal HI brain injury or the hemisection cavity in an adult SCI. Implantation of human NPC (hNPC)–scaffold complex reduced the lesion volume, induced survival, engraftment, and differentiation of grafted cells, increased neovascularization, inhibited glial scar formation, altered the microglial/macrophage response, promoted neurite outgrowth and axonal extension within the lesion site, and facilitated the connection of damaged neural circuits. Tract tracing demonstrated that hNPC–scaffold grafts appear to reform the connections between neurons and their targets in both cerebral hemispheres in HI brain injury and protect some injured corticospinal fibers in SCI. Finally, the hNPC–scaffold complex grafts significantly improved motosensory function and attenuated neuropathic pain over that of the controls. These findings suggest that, with further investigation, this optimized multidisciplinary approach of combining hNPCs with biomaterial scaffolds provides a more versatile treatment for brain injury and SCI. Tissue engineering: Repairing brain and spinal injuries Biodegradable scaffolds seeded with human fetal brain cells can help repair neurological injuries in rodents. A team led by Kook In Park and Il-Shin Lee from the Yonsei University College of Medicine in Seoul, South Korea, created a mesh of plastic fibers that they bathed in neural progenitor cells. Over the course of several days, these cells differentiated into different types of brain cells, including neurons and glia. The researchers implanted these cell-scaffold complexes into the sites of injury in two rodent models: newborn mice with oxygen deprivation to the brain, and adult rats with severed spinal cords. In both cases, the treatment helped the injured tissues heal and improved the neurological or motor function of the animals. The authors suggest these tissue-engineered structures could also help people with brain or spine injuries.